1997
DOI: 10.1074/jbc.272.36.22824
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation of Connexin 43 by v-Src Is Mediated by SH2 and SH3 Domain Interactions

Abstract: Reduction of gap junctional communication in v-The Rous sarcoma virus transforming protein, v-Src, and its cellular homologue, c-Src, are protein tyrosine kinases associated with the plasma membrane (1). Expression of v-Src leads to neoplastic cell transformation, accompanied by increased tyrosine phosphorylation of cellular proteins (2-4). Signaling through Src is due, in part, to protein-protein interactions mediated by SH2 1 and SH3 domains (5-7). Mutations in either the SH2 or SH3 domain of c-Src can lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
161
0
5

Year Published

1998
1998
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(178 citation statements)
references
References 92 publications
(126 reference statements)
12
161
0
5
Order By: Relevance
“…Previous studies have indicated that the SH3 domain of activated Src binds the CT domain of Cx43 near Pro-280 (44,45). Our data indicate that Src SH3 binding induces major structural changes in Cx43CT region Lys-264 -Lys-287, which extends upstream to the SH2 binding domain; presumably, these are the structural changes necessary for Tyr-265 phosphorylation.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Previous studies have indicated that the SH3 domain of activated Src binds the CT domain of Cx43 near Pro-280 (44,45). Our data indicate that Src SH3 binding induces major structural changes in Cx43CT region Lys-264 -Lys-287, which extends upstream to the SH2 binding domain; presumably, these are the structural changes necessary for Tyr-265 phosphorylation.…”
Section: Discussionmentioning
confidence: 50%
“…3). Only the region Lys-264 -Lys-287 contains the amino acids previously reported to act as an SH3 binding domain (43)(44)(45). Although all changes were consistent with SH3 binding and altering the structure of Cx43CT, the resonance peaks were affected in three different ways.…”
Section: Structural Changes In Cx43ctmentioning
confidence: 84%
“…By use of mutant src genes, several cellular proteins have been described as transformation-relevant substrates of v-Src kinase. These include; b-catenin (Hamaguchi et al, 1993a); glycoproteins of 95 kDa and 130 kDa (Hamaguchi et al, 1990;Kozuma et al, 1990); connexin-43 (Crow et al, 1992;Kanemitsu et al, 1997); 120-kDa protein (Linder and Burr, 1988). Thus, mutant src genes have been utilized as an e cient tool to characterize substrate proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Substitution of murine c-Src RT loop residues (Trp at Arg-97 and Ile at Thr-98) did not disrupt the binding of normal c-Src SH3 targets such as p130Cas (6). Instead, RT loop residue changes at Trp-97 promoted the binding of proteins such as connexin 43 and FAK to the c-Src SH3 domain (6,7). In FAK, the v-Src SH3 domain binding sites were mapped to three proline-rich motifs conforming to a PXXPXX consensus where is a hydrophobic residue (6).…”
mentioning
confidence: 99%
“…In FAK, the v-Src SH3 domain binding sites were mapped to three proline-rich motifs conforming to a PXXPXX consensus where is a hydrophobic residue (6). This extended PXXPXX motif differs from c-Src class I or class II SH3 binding motifs (5) and is conserved in other v-Src SH3 domain-binding proteins (7,8). Since the v-Src SH3 domain binds to additional targets compared with the c-Src SH3 domain, the RT loop substitutions can be considered gain-of-function mutations.…”
mentioning
confidence: 99%